MODEL OF BEHAVIOR OF PSEUDOELASTICITY MATERIAL UNDER NONSTATIONARY LOADING - Chernyakov, Yu. A.; Steblyanko, P. A.; Petrov, A. D. (Computer Science and Applied Mathematics, 2017)
The list of alloys that exhibit pseudoelasticity includes Ni-Ti alloys and various copper, iron, silver and gold-based alloys. Pseudoelasticity is the ability of a material to accumulate deformations upon loading at a high temperature regime and then return to its original state after unloading (through the hysteresis loop). The mechanism of this reduction is the transformation from the martensite phase to the original austenite phase. Such alloys as NiTi, CuZnAl, CuAlNi, AuCd and others can restore deformations up to 3%. Important characteristics of some of these materials are internal damping, pseudoelasticity and high yield strength. A nonstationary thermo-elastic-plastic problem is examined for bodies from pseudoelasticity material. The feature of theory consists of that the diagram of tension of deformations appears as three-unit broken and can have a handing down area. Thus the characteristic points of diagram depend on a temperature and phase state of material. Such character of diagram results in break decisions and as a result to the moving boundaries of phase transitions. The example of thin stripe is considered at monaxonic tension. It is shown that deformation is inhomogeneous according to bar and her development depends on properties of material. A version of the model of behavior of a pseudoelastic material has been developed and experimentally substantiated. In this model, the possibility of quantitative evaluation of the associated interactions between stresses, temperature, deformation and material loading rate is built that is suitable for modeling the continual level. We obtained the numerical confirmation that the front of the stepwise change in the strain propagates at a constant rate that depends only on the mechanical properties of the material. Recurrent formulas allow us to obtain the third (for temperature) and fourth (for the velocities of displacements, stresses and deformations) order of approximation of the method with respect to the coordinates.